Kualitas dan Interpretasi Hadis tentang Misogini: Studi Takhrij dan Syarah - Agustiani, Yupi; Ratnasih, Teti (Jurnal Riset Agama, 2022)
This study aims to discuss the hadith about misogyny. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about misogyny, in the narration of Bukhari no. 293. The results and discussion of this study indicate that the status of the hadith is of authentic quality that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Bukhari no. 293 is relevant to be used as motivation for early warning and the development of good behavior in worship.